1998
DOI: 10.5144/0256-4947.1998.497
|View full text |Cite
|
Sign up to set email alerts
|

AirborneAlternariaSpores: Potential Allergic Sensitizers in Saudi Arabia

Abstract: Background:In order to investigate the role of airborne Alternaria spp. in the sensitization of individuals having respiratory allergy symptoms, particularly bronchial asthma, an aerobiologic and clinical (diagnostic) study was conducted at several centers in Saudi Arabia. Materials and Methods: Airborne Alternaria spores were studied at four different centers in Riyadh, Jeddah and Al-Khobar, including three years at one site. Skin prick tests (SPT) were conducted on a total of 616 allergic individuals attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Licorish et al (1985), however, suggest that of the order of 10 4 -10 7 spores need to be inhaled over a 24-h period. Hasnain et al (1998) suggest that a mean daily concentration of 50 Alternaria spores/m 3 are needed to cause sensitisation, after which smaller concentrations can cause symptoms.…”
Section: Introductionmentioning
confidence: 97%
“…Licorish et al (1985), however, suggest that of the order of 10 4 -10 7 spores need to be inhaled over a 24-h period. Hasnain et al (1998) suggest that a mean daily concentration of 50 Alternaria spores/m 3 are needed to cause sensitisation, after which smaller concentrations can cause symptoms.…”
Section: Introductionmentioning
confidence: 97%
“…Ianovici et al (2013) cites Targonsky et al (1995), who described the atmospheric concentration of 2000 spores/m 3 as linear to Cladosporium spores, cause clinical symptoms. With regard to Alternaria spores, Ianovici et al (2013) cites Hasnain et al (1998), who suggested that clinical symptoms occur with atmospheric concentrations higher than 50 spores/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Fungal spores, due to their volume in the atmosphere and small size, have an important contribution to the respiratory allergies and cause various symptoms range from asthma, allergic rhinitis to bronchitis (Vijay et al1991, D'amato &Spieksma 1995, Hasnain et al, 1998. It has been demonstrated that the environmental factors such as meteorological and seasonal climatic factors Klarić & Pepeljnjak, 2006), the type of vegetation (Pepeljnjak & Šegvić, 2003), air pollution (Lin &Li, 2000), and human activities , affect the variety of air borne fungi.…”
Section: Introductionmentioning
confidence: 99%